1989
DOI: 10.1128/aac.33.10.1704
|View full text |Cite
|
Sign up to set email alerts
|

Structure-epileptogenicity relationship of quinolones with special reference to their interaction with gamma-aminobutyric acid receptor sites

Abstract: The relationship between the chemical structure and epileptogenic activity of quinolones was investigated. When the quinolones were administered intravenously to mice concomitantly with oral biphenylacetic acid, a major metabolite of the nonsteroidal antiinflammatory drug fenbufen, enoxacin, norfloxacin, ciprofloxacin, and pipemidic acid, which have an unsubstituted piperazine moiety at the 7 position of their parent nuclei, provoked clonic convulsions and subsequent death at doses of 6.25 mg/kg or more in a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
109
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(114 citation statements)
references
References 20 publications
5
109
0
Order By: Relevance
“…These signs subsided within several minutes in the affected dogs, and slower infusion (for 2-3 minutes) did not produce such severe clinical signs. Others (Akahane et al, 1989) reported that the epileptogenic activity of fluoroquinolones possibly relates to the γ-aminobutyric acid (GABA)-like structures of the substituents at position 7 of some of the fluoroquinolones, which may allow them to act as GABA-receptor antagonists. Furthermore, enrofloxacin has increased the frequency and intensity of seizures in epileptic dogs (Van Cutsem et al, 1990).…”
Section: Adverse Effectsmentioning
confidence: 99%
“…These signs subsided within several minutes in the affected dogs, and slower infusion (for 2-3 minutes) did not produce such severe clinical signs. Others (Akahane et al, 1989) reported that the epileptogenic activity of fluoroquinolones possibly relates to the γ-aminobutyric acid (GABA)-like structures of the substituents at position 7 of some of the fluoroquinolones, which may allow them to act as GABA-receptor antagonists. Furthermore, enrofloxacin has increased the frequency and intensity of seizures in epileptic dogs (Van Cutsem et al, 1990).…”
Section: Adverse Effectsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] Concerns were raised about the safety of FQs on the central nervous system. Although some studies have explored the potential mechanisms of FQ-induced seizure, [12][13][14][15] comprehensive epidemiologic data from populationbased studies are needed. The primary objective of this study was to investigate the relationship between FQs and incident seizures using data from Hong Kong (HK) and the United Kingdom (UK).…”
mentioning
confidence: 99%
“…It is usually asserted that these excitatory side effects result from inhibition of GABA (␥-aminobutyric acid) binding to its receptors (1,11). Using intracerebral microdialysis, however, Smolders et al have previously observed in conscious rats norfloxacin-induced convulsions accompanied not by any apparent effect on the extracellular hippocampal GABA levels but rather by enhanced intracerebral glutamate concentrations (10).…”
mentioning
confidence: 99%